An Empiric Analysis of Omaha System Targets - Monsen, K.; Melton-Meaux, G.; Timm, J.; Westra, B.; Kerr, M.; Raman, N.; Farri, O.; Hart, C.; Martin, K. (Applied Clinical Informatics, 2011)
Interface terminologies used in electronic health records must be re-evaluated and revised to reflect current health care practice and knowledge. To enable future revisions of the Omaha System Intervention Scheme, investigators evaluated formal semantic structure of target terms and concept duplication of problem and target terms. Using linguistic principles and qualitative analysis, five themes were found. A multidimensional formal semantic structure for the intervention target term was proposed. Concept duplication was examined for 16 problem-target matches. Clinical data enabled assessment of the validity of a proposed formal semantic structure and concept duplication. Recommendations are suggested for future development of the Omaha System Intervention Scheme.
Keywords: Omaha System; clinical data management standards; clinical care; system improvement; system improvement; evaluation; methologies; data analysis